Influence and characteristics of anticyclonic eddies in active MHW years in the Northwest Atlantic - Lydia D. Sims; Bulusu Subrahmanyam; Corinne B. Trott (Frontiers in Marine Science, 2023)
The Northwest Atlantic contains two subregions, the Gulf of Maine and the Mid-Atlantic Bight. This region is dynamically controlled by the Jet Stream, the Gulf Stream, (GS) and its eddies. Anticyclonic eddies (AEs) (warm core clockwise eddies) and cyclonic eddies (cold core counterclockwise eddies) influence oceanic properties as they are shed by the GS and dissipated in the Northwest Atlantic. Marine Heatwaves (MHWs) are extreme temperature events that cause ecological damage in the Northwest Atlantic where drivers for these events are abundant. This work focuses on four major MHW active years (2012, 2016, 2017, and 2020) and observes the characteristics of MHWs, AEs, and oceanic parameters, such as Ocean Heat Content, Mixed Layer Depth, temperature, and salinity anomalies. Depth profiles, lead-lag covariance and correlations, and comparisons of events reveal dynamics of MHW intensification in these four years. AE radius, amplitude, and eddy kinetic energy (EKE) were less variable in the MHW years of 2012, 2016, and 2017 but have a weak relationship with MHW intensity. The Gulf of Maine had the strongest (above 0.80) correlation between GS eddy heat flux convergence and MHW intensity. The 2012 MHWs were shown to be strongly influenced by the GS in addition to atmospheric forcings, as were the 2017 Gulf of Maine MHWs. The 2020 MHWs experienced a number of forcings from the Jet Stream, the GS, and AEs, with the highest intensity events occurring at depths below 100 m. We conclude that better understanding how regional dynamics and multiple drivers intensify MHWs to form MHW active years is key to modelling and forecasting future extreme events.